2020
DOI: 10.21203/rs.3.rs-15838/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Predictors of Anxiety and Depressive Symptoms among Patients Diagnosed with Oral Cancer in China: A cross-sectional study

Abstract: Background Anxiety and depression are common mental health problems among patients with cancer. While many psychological variables have been proven to influence anxiety and depressive symptoms, the variables are not mutually exclusive and their integrated effects on patients with oral cancer are yet unknown. The present study aims to explore the prevalence of anxiety and depressive symptoms among patients with oral cancer, to find out key potentially predictive factors associated with anxiety and depressive sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Table 4 illustrates the mental well‐being and financial toxicity of studies from the pre‐pandemic era. Depression rates ranged from 17% to 65%, Anxiety rates ranged from 20% to 35% 14–16 . Our study shows depression among 58.2% and anxiety in 72.2%.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Table 4 illustrates the mental well‐being and financial toxicity of studies from the pre‐pandemic era. Depression rates ranged from 17% to 65%, Anxiety rates ranged from 20% to 35% 14–16 . Our study shows depression among 58.2% and anxiety in 72.2%.…”
Section: Resultsmentioning
confidence: 52%
“…Lulu Yuan et al. reported that the prevalence of anxiety symptoms and depressive symptoms were 36.96% (85/230) and 65.21% (150/230), respectively 15 . William F Pirl et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer and its treatments frequently cause physical and mental disorders in patients. The leading problems of cancer patients are stress, depressive symptoms, anxiety, hopelessness, fear, sadness, and aggression (Alagazy, Soltan & Soliman, 2020;Dehghan et al, 2020;Handbook/Brest cancer, 2021, p.1-6;Prabath & Ruban, 2020;Weeratunga, Senadheera & Ekanayake, 2016;Weeratunga et al, 2019;Weeratunga et al, 2021;Yan, Chen & Li, 2019;Yuan, Pan & Wang, 2020). Not only cancer, its related factors such as social activities, different coping strategies (Finck et al, 2018;Weeratunga et al 2022), work, and childcare also affect the QoL (Yusoff et al, 2022).…”
Section: Introductionmentioning
confidence: 99%